"Wholeness Is No Trifling Matter": Toward an Epistemology of Care, Touch, and Celebration in Education - Wilson K. Okello; Shawn S. Savage (MDPI AG, 2024)
The authors argue that embracing life necessitates a shift in how we conceptualize wellness in education. They delve into the exploration of humanizing wellness and living well by drawing on Black onto-epistemologies, specifically referencing Bambara's The Salt Eaters. This exploration involves examining how notions of wholeness manifest in the text and the subsequent implications for educators and scholars actively involved in anti-equity efforts. The authors elucidate both the possibilities and challenges related to care, touch, and celebration. In particular, they employ the concept of Black refusal to investigate how these elements can propel a critical departure from conventional ideas of wellness in the United States, paving the way for alternative modes of existence which prioritize wholeness. To achieve this, the authors present an exploration of the literature on whiteness, epistemology, and the destructive impact of anti-Blackness. The authors then introduce Black refusal as a theoretical framework, which functions as the frame guiding their methods. Examining personal reflective instances of engagement with the present political landscape, analyzing Bambara's The Salt Eaters, and maintaining refusal as a central theoretical framework, the authors detail an epistemology of wholeness centered on care, touch, and celebration.